Shifting Consumer Behavior Towards Modern Meat Outlets in Majene West Sulawesi - Adli Putra Ermanda; Nita Adillah Pratiwi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This study investigates the shift in consumer purchasing patterns from traditional markets to modern meat outlets in Majene Regency, a region located in a province with a low Human Development Index (HDI) but designated as an educational center in West Sulawesi, Indonesia. In recent years, Majene has seen an influx of expatriatess with higher education, knowledge, and income, likely influencing local purchasing behaviors. This research examines the factors contributing to the observed shift in meat purchasing patterns, focusing on cultural, social, personal, and psychological factors that affect purchasing decisions. Data were collected from 100 respondents, all homemakers, over one month from June to July 2024. Homemakers were chosen due to their primary role in household purchasing and decision-making regarding market selection and meat processing. Structural Equation Modeling with Partial Least Squares (SEM PLS) analysis was conducted using WarpPLS 7.0 software to determine the influence of cultural (X1), social (X2), personal (X3), and psychological (X4) factors on purchasing decisions (Y). The results indicate that psychological factors exert the highest level of significance on purchasing decisions, with a coefficient of 0.557, followed by cultural factors (0.165), social factors (0.050), and personal factors (-0.082). The prominence of psychological factors may be attributed to the profile of respondents, many of whom are lecturers and private sector employees from outside Majene. This demographic shift and perceptions of higher quality and safety at modern outlets have encouraged transitioning from traditional markets to modern meat outlets. These findings contribute to understanding consumer behavior changes in small-city contexts and offer insights into the role of psychological and demographic factors in shaping retail preferences in developing regions.